Facts and doubts about the beginning of human life Human embryo : a critical approach to bioethical reason A catholic perspective - Abel, Francesc (Array, 2009)
We can say that the human embryo is the structure that develops from a human zygote, through a series of divisions, differentiated into tissues and organs. The human zygote is the founding cell of an organism, resulting from the meeting of two specialized cells called gametes, one from the mother (egg) and one from the father (sperm). Each of these has been duly prepared over a long process (meiosis), which leads, as the most relevant and visibly noticeable fact of the last phase of ripening, to the systematic reduction of the number of chromosomes from 46 to 23. Curiously, these gametes cannot survive separately for very long, only a few hours, but following syngamy, their fusion gives rise to a new human life different from that of its parents, that lasts for years. Fertilization takes place in the upper third of the Fallopian tube and first affects the cytoplasm of the gamete cells and then their nuclei, thus marking the two most relevant aspects of gamete fusion